Does Stroke Impair Learning in Children? - Sonia das Dores Rodrigues; Sylvia Maria Ciasca; Inês Elcione Guimarães; Karla Maria Ibraim da Freiria Elias; Carolina Camargo Oliveira; Maria Valeriana Leme de Moura-Ribeiro (Stroke Research and Treatment)
Objective. To assess cognitive development and learning in children who have had strokes. Method. Twenty-nine stroke patients and 18 children with no brain lesions and no learning impairments were evaluated. For the cognitive assessment, Piaget's clinical method was used. Writing, arithmetic, and reading abilities were assessed by the school performance test. Results. The mean age at evaluation was 9.6 years. Among the 29 children, 20 had early lesions (mean of 2.4 years old). The stroke was ischemic in 18 subjects; there were 7 cases of recurrence. Six children could not answer the tests. A high index of cognitive delay and low performance in writing, arithmetic, and reading were verified. Comparison with the control group revealed that the children who have had strokes had significantly lower performances. Conclusion. In this sample, strokes impaired cognitive development and learning. It is important that children have access to educational support and cognitive rehabilitation after injury. These approaches may minimise the effects of strokes on learning in children.